(3NWC aj MjGJj (B/s - (3GdYdjGf, beGTI YHO GdQMef UGdMs ((3GdOeGe (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3OGQ GdcaGM ddfTQ hGdJhRjY ,s, 2005)
(3JSJYQV eLehYI (B"(3NWC aj MjGJj(B" (3dbeGTI GdYdjGf eLehYI ef GdbUU GdJj JJfGhd ehGVjY GdfOe hGdGNJjGQGJ GdMjGJjI, MjK JJaGYd TNUjGJgG eY dMXGJ MGSeI aj MjGJge JDKQ Ydi eSGQGJge HTcd cHjQ, JSdW GdcGJHI GdVhA Ydi cjajI ehGLgI GdCaQGO ddCNWGA GdJj GQJcHhgG hcja JDKQ gPg GdCNWGA Ydi YdGbGJge heTGYQge, JJejR GdcJGHI HdZI HSjWI hYejbI JYcS GdCHYGO GdfaSjI dcd TNUjI, eeG jLYd GdbGQF jTYQ HGdJYGWa hGdGQJHGW HJLGQHge, JbOe GdeLehYI QDi eJYOOI Mhd eaghe GdNWC hcja jecf Cf jDOj Edi GdOQhS GdeSJaGOI hGdfeh GdTNUj, JYcS (B"(3NWC aj MjGJj(B" (3QMdI GdHMK Yf Gdage hGdZaQGf, eeG jLYdgG YedG COHjG jMaR GdJacjQ hGdJCed aj JLGQH GdMjGI(B.s
Keywords: (3GdbUU GdYQHjI GdbUjQIs